PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP KEKUATAN OTOT DAN KUALITAS TIDUR LANJUT USIA - Muhith, Abdul; Herlambang, Teguh; Fatmawati, Atika; Hety, Dyah Siwi; Merta, I Wayan Surya (Universitas Tribhuwana Tunggadewi, 2020)
Physiological changes in the elderly can cause a change in the neural system that is a disorder towards sleep quality while changes in the musculoskeletal system are the occurrence of muscle strength decline. Progressive Muscle Relaxation Therapy is a therapy which can improve sleep quality and muscle strength. The purpose of this research is to analyze the effect of progressive muscle relaxation therapy towards muscle strength and sleep quality of the elderly at House Technical Implementation. The research type used is quasi-experiment design with pretest and posttest nonequivalent control group design. The population in this research were all elderly as many as 40 elderly people. The sampling technique used was Total Sampling which was then divided into intervention group which consists of 20 respondents and control group which consists of 20 respondents. The measurement tool used was PSQI (Pittsburgh Sleep Quality Index) questionnaire for sleep quality and the MMT (Manual Muscle Testing) observation sheet for muscle strength. The data were analyzed using Paired T-test and Independent T-test. Based on Paired T-test, it was obtained that p value = 0.000 (p